The effect of horticultural therapy on depressive symptoms among the elderly: A systematic review and meta-analysis - Zhang, Ya Wei; Wang, Jun; Fang, Tian Hong (Frontiers in Public Health, 2022)
Objective This systematic review and meta-analysis aimed to assess the effectiveness of horticultural therapy on depressive symptoms in the elderly and determine the potential moderators of the intervention effect. Methods In early June 2022, randomized controlled trials and Quasi-experimental studies were searched on Web of Science, PsycINFO, CINAHL, EMBASE, Medline, PubMed, CNKI, WANFANG DATA, and CQVIP. Three independent authors proposed the following inclusion criterion for this study: the elderly with applied horticultural therapy intervention compared to non-HT intervention. From a total of 3,068 records, only 34 studies met the inclusion criteria. After the full-text screening, 13 studies were included in the analysis. An assessment of the risk of bias was conducted using RoBINS-I and RoB 2 tools. The comprehensive Meta-Analysis 3.3 tool was used for the meta-analysis. Results Meta-analysis suggested that mean depression scores of elderly people who underwent horticultural therapy intervention were significantly lower than those who did not receive HT therapy. More significant effects were found for the elderly with mean age equal to or over 75 years instead of younger than 75 years, in randomized controlled trials instead of quasi-experimental studies, for studies with more than 20 participants receiving horticultural therapy at the same time and place instead of equal to or fewer than 20 horticultural therapy participants. Conclusions This evidence supported that horticultural therapy had a significant positive effect on the depressive symptoms outcomes for the elderly. Therefore, our data revealed that horticultural therapy could be considered as a part of therapy in depressive symptoms reduction programs. Due to the high degree of heterogeneity and the limited number of studies, a future review is warranted to determine the effects of horticultural therapy on depressive symptoms reduction in the elderly. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=272464, identifier: CRD42021272464.